Using zeta potential to study the ionisation behaviour of polymers employed in modified-release dosage forms and estimating their pKa - Joao A.C. Barbosa; Malaz S.E. Abdelsadig; Barbara R. Conway; Hamid A. Merchant (International Journal of Pharmaceutics: X, 2019)
A range of enteric polymers is used in pharmaceutical industry for developing gastro-resistant formulations. It is generally implied that these coatings are interchangeable due to similar dissolution pH thresholds reported by suppliers. Despite rapid dissolution in compendial phosphate buffers, these products can take up to 2 h to disintegrate in-vivo in the human small intestine. The factors primarily responsible for such variability in dissolution of these polymeric coatings are the differences in ionisation of acidic functional groups on polymer chains and their interplay with ions and buffer species present in gastrointestinal fluids. In this study, we aim to develop a novel, simple and inexpensive technique that can be used under various in-vitro conditions to study the ionisation behaviour of commonly used polymers (EUDRAGIT-E100, L100, S100, HPMC AS-LF, AS-HF, HP-50, HP-55) and to estimate their pKa. Moreover, this method was successfully applied to study the ionisation behaviour of a range of natural polymers (Guar, Tara, locust bean, Konjac gums, gum Arabic, citrus pectin, chitosan and alginate) and their pKa was also estimated. The proposed method would allow a better understanding of the dissolution behaviour of these polymers within gastrointestinal tract and will aid rational design of modified release dosage forms. Keywords: pKa, Ionisation, Enteric, Gastro-resistant, Modified-release, Zeta-potential, Charge, Dissolution